Effect of dietary cholesterol content on growth and its accumulation in liver and muscle tissues of juvenile yellowtail kingfish (Seriola lalandi) - Fernando M Guerra-Olvera; María Teresa Viana (Ciencias Marinas, 2015)
A feed trial conducted with juvenile yellowtail kingfish (Seriola lalandi) was designed to address the effect of dietary cholesterol content on growth performance and the cholesterol concentration in liver and muscle. For 60 days fish were fed four diets based on defatted fish meal, soy protein concentrate, cholesterol-free fish oil, canola oil, and olive oil, with four different concentrations of cholesterol (treatments Ch0.0, Ch0.05, Ch0.12, and Ch0.19 containing 530, 2880, 4120, and 6170 mg kg–1 of crude fat, respectively). After 60 days, maximum weight gain was obtained with diet Ch0.05, and it was significantly higher than that obtained with diets Ch0.0 and Ch0.19, but not different from that obtained with Ch0.12. Cholesterol concentration in liver and muscle tissues was not affected by the diet, showing no significant differences among dietary treatments with levels reported as normal. Though cholesterol biosynthesis could not be measured in the present work, we discuss the possibility that fish are able to synthesize cholesterol when fed diets containing no or less cholesterol than required, but at the expense of energy consumption, limiting fish growth. We conclude that cholesterol content in aquafeeds affects fish growth when diets are formulated with vegetable ingredients, and the optimal content should be between 2880 and 4120 mg kg–1 of crude fat to avoid consequent cholesterol accumulation in liver or muscle tissues.